The Effectiveness Of Inquiry Learning Communication On Student Learning Outcomes At Smpn 2 Makassar - Evi Nurfawali Asbar; Tuti Bahfiarti; Muhammad Farid (Sahafa Journal of Islamic Communication, 2022)
AbstractThetransition from onlineto offlinelearning occurred during the covid-19 pandemic; this madestudents need time to adapt to the learning process. Therefore, innovation in learning is needed, especially in science subjects, where teachers can choose the suitable learning method; one method that can be used is the inquiry learning method. Thisstudy aimsto: (1) analyzetheeffectiveness of inquiry learning communication on student learning outcomes in science subjects in public junior high school 2 Makassar, and (2) analyze the effect of inquiry learning communication on student learning outcomes in science subjects in secondary schools. The first istheland of 2 Makassar cities. The method used in thisstudy is quantitative with a descriptive correlation approach. The sample in this study amounted to 144 class VIII students with the cluster random sampling technique. The data collection technique used a closed questionnaire with a Likert scale. The results showed that (1) the effectiveness of inquiry learning communication affected student learning outcomes in science subjects at public junior high school 2 Makassar. There is a change in student behavior due to the stimulus carried out by the teacher during the learning process, and (2) There is a positive and significant influence of inquiry learning communication on student learning outcomes. The simple linear regression analysis results show the R Square value of 0.380. This shows that the effect of variable X (effectiveness of inquiry learning communication) on variable Y (student learning outcomes) is 38.0%. AbstrakMasa transisi pembelajaran daring menjadi luring terjadi saat pandemi covid-19, hal ini membuat peserta didik membutuhkan waktu untuk beradaptasi kembalidalam prosespembelajaran. Maka dari itu, dibutuhkan adanya inovasi dalam pembelajaran terutama pada pelajaran IPA (Ilmu pengetahuan Alam), dimana guru bisa memilih metode pembelajaran yang sesuai, salah satunya yaitu metode pembelajaran inkuiri.Adapun tujuan dari penelitian ini, yaitu untuk: (1) menganalisis efektivitas komunikasi pembelajaran inkuiri terhadap hasil belajar siswa pada pelajaran IPA di SMPN. 2 kota Makassar, dan (2) menganalisis pengaruh komunikasi pembelajaran inkuiri terhadap hasil belajar siswa pada pelajaran IPA di SMPN. 2 kota Makassar. Adapun Metode yang dapat digunakan dalam penelitian ini adalah kuantitatif dengan pendekatan penelitian deskriptif correlation. Sampel penelitian ini berjumlah 144 siswa kelas VIII dengan teknik cluster random sampling. Teknik dalam mengumpulkan data menggunakan angket tertutup dengan skala likert. Hasil penelitian ini menunjukkan bahwa (1) Efektivitas komunikasi pembelajaran inkuiri berpengaruh terhadap hasil belajar siswa pada pelajaran IPA di SMPN 2 kota Makassar. Dapat dilihat bahwa terdapat perubahan perilaku peserta didik yang diakibatkan karena adanya stimulus yang dilakukan oleh komunikator(guru) pada proses pembelajaran yang berlangsung, dan (2) ada pengaruh positif dan signifikan komunikasi pembelajaran inkuiri terhadap hasil belajar siswa. Berdasarkan hasil uji analisis regresi linear sederhana menunjukkan bahwa nilai R Square adalah sebesar 0,380. Hal ini menunjukkan ada pengaruh efektivitas komunikasi pembelajaran inkuiri (Variabel X) terhadap hasil belajar siswa (variabel Y) dengan nilai sebesar 38,0%.